Sodium intake in Italy from 2008 to 2019: results of the CUORE Project-Health Examination Surveys. (30th September 2020) - Donfrancesco, C; Lo Noce, C; Russo, O; Bellisario, P; Galeone, D; Vannucchi, S; Giampaoli, S; Galletti, F; Palmieri, L; Strazzullo, P
Abstract: Background: The WHO Global Action Plan for the Prevention of NCDs recommends a 30% relative reduction in mean population intake of salt/sodium. To this end, the Italian Ministry of Health (MoH) has strengthened prevention and health promotion through the "Gaining health: making healthy choices easy" Programme and the National Preventive Plan 2014-2019, in collaboration with the Interdisciplinary Working group for Salt Reduction in Italy. To estimate the habitual salt intake and its trend in the general adult population, national surveys, funded by the MoH-CCM, are conducted within the CUORE Project. Methods: Baseline salt intake by the use of 24h urine collections was assessed in 2008-2012 from representative random samples of residents in all Italian Regions. A new survey was conducted in 2018-2019 involving random samples of residents in 10 Regions. Urinary sodium excretion is assayed by a central lab at Federico II University of Naples, subjected to strict quality controls. Comparisons are made considering, for both periods, the first seven regions examined in the 2018-2019 survey and the age range of 35-74 years. Results: Within the 2008-2012 survey, mean level of sodium chloride per day in 642 men and 627 women were 10.6 g (10.3-11.0 g) and 8.0 g (7.7-8.3 g) respectively, whereas in the 2018-2019 survey the corresponding mean levels in 673 men and 709 women were 9.3 g (95% C.I.: 9.1-9.6 g) and 7.1 g (6.9-7.3 g), respectively. A sodium chloride intake level lower than the WHO recommended target of 5g/day (or 85 mmol/day) was detected in 5% (3-6%) of men and 16% (13-19%) of women examined in 2008-2012 vs 9% (6-11%) of men and 24% (20-27%) of women examined in 2018-2019. Conclusions: These preliminary data show that the average habitual sodium intake in Italy is still higher than recommended but a significant reduction seems to occur. These results fully justify and encourage the ongoing preventive initiatives of MoH, facilitating the meeting of the WHO-NCD target. Key messages: Habitual salt intake in the Italian general adult population is still higher than the recommended by the WHO. If confirmed, in the last ten years a reduction of habitual salt intake in Italian general adult population seems to be occurred.